Supply Chain Management Practices in Response to Ecosystem Challenges – A Narrative Literature Review - El Hajjaji, Ihssane; Rahmani, Hasnae (European Scientific Journal, ESJ, 2025)
In recent years, there has been a widespread awareness of issues affecting the ecosystem, such as climate change. It is, in fact, a universal reality that affects human life, business activities, and the environment. In this context, companies are required to master the functioning of a dynamic and risky ecosystem where logistics play a very important role in meeting sustainable development objectives. Purpose: The objective of this article is to identify the main supply chain management practices that enable companies to address the challenges of the ecosystem and their impact on the environment and global performance, with a focus on the implications of climate change. This research aims to analyze the impact of these practices on business performance. Methodology: This research adopts a narrative review of the literature based on scientific databases, using a search equation incorporating keywords. Articles were selected according to clearly defined inclusion and exclusion criteria to ensure the relevance and quality of the work analyzed. Results: The results show that adopting green practices in the supply chain, such as responsible sourcing, flow optimization, and the use of sustainable technologies, enables companies to respond to ecosystem challenges, better cope with the risks posed by climate change, and improve global performance. Implications: This study offers a comprehensive and up-to-date overview for researchers wishing to further explore the link between green supply chain practices and adaptation to ecosystem challenges. The results highlight the importance for companies to quickly adopt sustainable practices in order to preserve the ecosystem, strengthen their resilience, and contribute to the transition to more responsible supply chains. Originality/value: This review provides an integrated view of the supply chain practices used to respond to the challenges of climate change. It highlights their role in improving environmental performance and offers ideas for sustainable logistics management in a changing ecosystem.